2013
DOI: 10.15407/ujpe58.01.0040
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and High-Frequency Properties of Compensated GaN under Electron Streaming Conditions

Abstract: Conditions required for the streaming effect and the optical-phonon transit-time resonance to take place in a compensated bulk GaN are analyzed in detail. Monte Carlo calculations of the high-frequency differential electron mobility are carried out. It is shown that the negative dynamic differential mobility can be realized in the terahertz frequency range, at low lattice temperatures of 30-77 K, and applied electric fields of 3-10 kV/cm. New manifestations of the streaming effect are revealed, namely, the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Analyzing the peculiarities of THz-light transmission, the spectra of dynamic mobility will be used from ref. [13]. The spectra of , coefficients appear to be more significant at a higher electron concentration.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Analyzing the peculiarities of THz-light transmission, the spectra of dynamic mobility will be used from ref. [13]. The spectra of , coefficients appear to be more significant at a higher electron concentration.…”
Section: Resultsmentioning
confidence: 89%
“…We apply the theory developed in the section 2 to the film of compensated GaN of cubic modification with the following parameters: concentration of ionized impurity [13], and it was shown that at these parameters OPTTR is most pronounced within the range of the applied electric fields 2 to 8 kV/cm. The low-field mobility  was found to reach the values around 5000 cm 2 /(Vs) (corresponding scattering time ps 57 .…”
Section: Resultsmentioning
confidence: 99%
“…For calculations of electron transport characteristics we used the single-particle algorithm of the Monte Carlo procedure [20,22,23,38]. Three main scattering mechanisms were taken into account: electron scatterings by ionized impurities, acoustic phonons and polar optical phonons.…”
Section: Figure 1 Should Be Placed Herementioning
confidence: 99%
“…In contrast to conventional A III B V materials, such as GaAs, InSb or InP, the widebandgap nitrides (for GaN the bandgap is 3.2 eV) are described by the large separation between the lower Г-valley and upper valleys separation (~1.2…1.5 eV for GaN), the high optical phonon energy, ћω0 (for GaN, ћω0 ≈ 92 meV), the strong electron-optical-phonon coupling (the Fröhlich constant is ~0.4 for GaN) and the high low-field mobility (at room to liquid nitrogen temperatures the mobility is ~1500…5000 cm 2 /V•s for GaN, [15]). These material properties of the nitrides are favorable for the realization of a specific streaming-like electron transport regime, which is characterized by a quasi-periodic electron motion in the momentum space [16][17][18][19][20] due to the threshold character of the electron-optical phonon emission. The streaming transport regime is possible at low lattice temperatures, T0, (kBT0 < ћω0, where kB is the Boltzmann constant) and small electron concentrations, Ne.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we investigated conditions of streaming and OPTTR effects in the case of compensated GaN, where an undesirable influence of the non-elastic e e  scattering [10] can be avoided. We specified intervals of applied electric fields E (3…10 kV/cm), ambient temperatures T (30…150 K) and frequency ranges (0.2…2 THz), where streaming and OPTTR effects can occur [13,14]. Also, we investigated high-frequency properties of the compensated GaN under streaming conditions in the case of applied parallel magnetic field ( E H || ) [15,16] and found that this field has no effect on steady-state characteristics but essentially changes the frequency spectra of dynamic mobility tensor.…”
Section: Introductionmentioning
confidence: 99%